Strategi Implementasi Kebijakan Pengawasan dalam Pengelolaan Limbah Bahan Berbahaya dan Beracun di Kabupaten Purwakarta - Rini Oktoyani; Ely Sufianti; Hendrikus T. Gedeona (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2023)
Industrial development has a positive impact on the economy and a negative impact on health and the environment. The implementation of monitoring policies in hazardous waste management in Purwakarta Regency has not been optimal. This is marked by complaints of hazardous waste pollution from the public, industries that have not submitted hazardous waste management reports to DLH Kabupaten Purwakarta, many industries do not yet have a hazardous waste management permit, and there are still industries that are under the monitor of DLH Kabupaten Purwakarta regarding violations of hazardous waste management. This research uses descriptive qualitative method. The results of this study obtained the provision of incentives in the form of Properda, the application of administrative sanctions, methods and technical monitoring carried out internally and externally. DLH Kabupaten Purwakarta has limited resources and autonomy. In addition, the information submitted offline and the environmental management information system has not yet been integrated, particularly hazardous waste management among related stakeholders. DLH Kabupaten Purwakarta does not yet have regional regulations derived from the work copyright law. In the implementation of monitoring policies in hazardous waste management in Purwakarta Regency, the supporting factors are the provision of incentives and the inhibiting factors are limited resources, autonomy, and information. Therefore, it is hoped that the DLH Kabupaten Purwakarta will use the concept of collaborative governance in the implementation of monitoring policies in hazardous waste management.